DİABETİK HASTALARDA FEMOROPOPLiTEAL VEYA FEMOROTİBİAL BYPASS: ORTA DÖNEM TAKİP SONUÇLARI - KÖKSAL, Cengiz; BEŞİRLİ, Kazım; BOZKURT, A. Kürşat; KAYNAK, M. Kamil; CANGEL, Uğur; SAYIN, Ayla (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Thirty-fiw patients with diabetes mellitus underwent 30 femoropopliteal and 5 femorotibial bypass procedure. This group was matched with 35 cohort of patients without diabetes mellitus which were selected from the vascular database. Results.- Cumulatiw patency in diabetics for 1 and 3 years were 88.6% and 77.1% respectiwly. The results in non diabetics were 91.4% and 84.4%, respectiwly (p>0.05). Six minor and 3 major amputations had to be performed on diabetics contrary to the 2 minor and 1 major amputations in non-diabetics (p<0.05). Conclusion.- Results achiewd in diabetic group were not statistically significant than the non-diabetic group although amputation rate was found higher in the former.